Protective ceramic coating for corrosive environment
By using nanomaterial composites and a low-viscosity system design, the adhesion and application problems of traditional coatings in corrosive environments have been solved, achieving a highly efficient, environmentally friendly, and long-lasting anti-corrosion effect.
Patent Information
- Application Number
- CN202511022232.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-24
- Publication Date
- 2025-11-07
AI Technical Summary
Traditional anti-corrosion coatings have insufficient adhesion and poor solvent resistance in corrosive environments. The construction process relies on organic solvents and has a long curing cycle, making it difficult to meet the requirements for long-term protection and resulting in high operation and maintenance costs and safety risks.
In-situ polymerization technology is used to combine two-dimensional sheet-like nanomaterials with one-dimensional nanomaterials to construct a multi-layered protective structure. The system of low-viscosity epoxy resin and modified amine curing agent is optimized, and functional pigments and fillers are screened to achieve rapid curing at room temperature and high-performance coating.
The coating adhesion is improved by 40%, the wear resistance is enhanced by 3 times, the construction efficiency is increased by 50%, the operation and maintenance cost is reduced by 40%, the anti-corrosion life is more than 20 years, it can adapt to complex scenarios and has no VOC emissions.
Smart Images

Figure CN120904758A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of protective coatings, and particularly relates to a protective ceramic coating for corrosive environments. BACKGROUND
[0002] With the acceleration of global industrialization and the increasing strictness of environmental protection regulations, the corrosion protection of chemical wastewater pipelines and treatment facilities has become a key challenge to the sustainable development of the chemical, energy, and municipal industries. The chemical wastewater is rich in strong solvents such as toluene and xylene, as well as acidic media such as chloride ions and sulfate ions, and solid suspensions, which cause serious chemical corrosion, erosion and wear, and electrochemical corrosion to metal pipelines and concrete structures during long-term operation, resulting in frequent accidents such as pipeline perforation and pool leakage. Traditional anti-corrosion coatings are difficult to meet the long-term protection requirements in complex corrosive environments due to their defects such as insufficient adhesion, poor solvent resistance, reliance on organic solvents during construction, and long curing period, which not only causes frequent maintenance and replacement and high operation and maintenance costs, but also poses the risk of leakage of toxic and harmful substances polluting the soil and groundwater, and causing safety accidents, and therefore, material innovation and process upgrading are urgently needed to achieve a technological breakthrough. SUMMARY
[0003] The present application discloses a protective ceramic coating for corrosive environments, which provides a high-adhesion solvent-free ceramic coating protection technology. The technology realizes the synergistic compounding of two-dimensional sheet-shaped nanomaterials (such as graphene and boron nitride) and one-dimensional nanomaterials (such as carbon nanotubes and whiskers) through in-situ polymerization technology, constructs a multi-level protection structure of "physical barrier + mechanical enhancement", and solves the problems of uneven dispersion of nanomaterials and insufficient interfacial bonding force; optimizes the low-viscosity epoxy resin and modified amine curing agent system to realize rapid curing and thick coating film formation under normal temperature conditions, breaking through the bottleneck of high-viscosity construction of traditional solvent-free coatings; and selects functional pigments and fillers such as ceramic powder and silane coupling agent to significantly improve the chemical corrosion resistance, hydrophobicity, and wear resistance of the coating. Through detection, the adhesion of the coating to the concrete substrate is ≥2.5 MPa, and to the metal substrate is ≥12 MPa, the wear resistance is ≤8 mg (Taber abrasion for 500 turns), the salt spray resistance test lasts more than 1000 hours without corrosion, and the corrosion protection period can reach more than 20 years, all of which are superior to traditional epoxy and polyurethane coatings.
[0004] The protective ceramic coating strictly follows the "Building Anti-corrosion Engineering Construction Specification" (GB 50212-2014) and the "Industrial Building Anti-corrosion Design Standard" (GB / T 50046-2018). Practice shows that the wastewater pipeline using the protective ceramic coating has a reduction of more than 40% in operation and maintenance cost under the long-term erosion of strong acidic medium and oily wastewater, and no leakage accidents have occurred; the solvent-free formula realizes zero VOC emission, and the construction process does not require high-temperature curing equipment, which can be adapted to complex scenes such as urban dense areas and marine engineering, and has high efficiency and environmental friendliness.
[0005] To achieve the above object, the technical scheme of the present application is:
[0006] A protective ceramic coating for corrosive environment is made of the following components with mass percentage: 30-40% of epoxy resin; 40-45% of ceramic powder; 10-25% of nano-material surface oxide; 5-10% of curing agent; 1-2% of silane coupling agent; 20-25% of two-dimensional sheet nano-material; and 10-15% of one-dimensional functional nano-material.
[0007] Preferably, the epoxy resin is E-44 and / or E-55 with mass percentage of 30% or 35% or 40%.
[0008] Preferably, the ceramic powder has mass percentage of 40% or 45%.
[0009] Preferably, the two-dimensional sheet nano-material is graphene and / or boron nitride with mass percentage of 20% or 25%.
[0010] Preferably, the one-dimensional functional nano-material is carbon nanotube and / or whisker with mass percentage of 10% or 15%.
[0011] Preferably, the curing agent is modified amine curing agent with mass percentage of 5% or 10%.
[0012] Preferably, the silane coupling agent has mass percentage of 1% or 2%.
[0013] Preferably, in the protective ceramic coating, the base material is the total of epoxy resin, ceramic powder, nano-material surface oxide, silane coupling agent, two-dimensional sheet nano-material and one-dimensional functional nano-material, and the mass ratio of base material to curing agent is 10:7.
[0014] A preparation method of a protective ceramic coating for corrosive environment, comprising the following steps:
[0015] Step 1, raw material pretreatment;
[0016] Step 2, base material preparation;
[0017] Step 3, base material and curing agent compounding.
[0018] Preferably, the step 1 comprises:
[0019] (11) Epoxy resin: preheat in 40℃ oven for 2 hours;
[0020] (12) Ceramic powder: filter through 1200 mesh screen to remove agglomerated particles and ensure uniform particle size;
[0021] (13) Two-dimensional sheet nanomaterials: surface modification with 3% to 5% of the mass of the two-dimensional sheet nanomaterials of silane coupling agent, namely: two-dimensional sheet nanomaterials and silane coupling agent in anhydrous ethanol for 30 minutes, keep the speed of 500 r / min, then 60 ℃ drying and standby;
[0022] (14) One-dimensional functional nanomaterials: surface modification with silane coupling agent by the same method as step (13);
[0023] (15) Curing agent: 2 ℃ to 8 ℃ sealed refrigeration, before use to restore to room temperature.
[0024] Preferably, the step 2 comprises:
[0025] (21) Pre-mixing of epoxy resin and silane coupling agent: add epoxy resin to the container, add silane coupling agent at a low speed of 500 r / min, stir for 10 minutes;
[0026] (22) Add nanomaterial surface oxide and ceramic powder for primary dispersion: gradually add nanomaterial surface oxide and ceramic powder to the stirring material obtained in step (21), increase the stirring speed to 1000 r / min, and continue for 2 minutes;
[0027] (23) Add two-dimensional sheet nanomaterials to the stirring material obtained in step (22) and high-speed shear dispersion: first stir at a low speed of 800 r / min for 5 minutes to allow the material to soak, then increase the speed to 2500 r / min for 30 minutes;
[0028] (24) Add one-dimensional functional nanomaterials to the stirring material obtained in step (23) and stir for compounding: adjust the speed to 1500 r / min and stir for 40 minutes;
[0029] During the steps (21) to (24), the container keeps the stirring material temperature ≤50 ℃ through temperature control.
[0030] Preferably, the step 3 comprises:
[0031] (31) Metering: weigh the base material and the curing agent according to the mass ratio "base material: curing agent = 10:7";
[0032] (32) Mixing and stirring: slowly pour the curing agent into the base material, initially stir at 800 r / min for 5 minutes; increase the speed to 1200 r / min and continue stirring for 15 minutes until the color of the system is uniform;
[0033] (33) Maturation and detection: after mixing, stand for 5 minutes, detect the viscosity, if the viscosity is high, extend the stirring time by no more than 10 minutes, control the total operation time to avoid premature reaction of the curing agent.
[0034] The protective ceramic coating for a corrosive environment has the following advantages:
[0035] The protective ceramic coating adopts a nano multi-layer composite design. Different nano materials of different nano dimension scales are mixed by superimposing and combining to make different nano layers bear the functions of wear resistance, corrosion resistance, and high temperature resistance, so as to achieve the nano multi-layer composite design. Through the screening of functional materials, the adhesion and the rapid construction at room temperature are improved, and the protective ceramic coating can be applied to various protective environments and is long-acting, safe, and environmentally friendly.
[0036] 1. Nano composite structure design, multi-layer cooperative protection:
[0037] Through in-situ polymerization technology, two-dimensional sheet-shaped nano materials (such as graphene and boron nitride) are compounded with one-dimensional functional nano materials (such as carbon nanotubes and whiskers) to build a multi-layer protective structure of “physical barrier + mechanical reinforcement”.
[0038] Physical barrier: the two-dimensional material forms a dense layer, delaying the penetration of corrosive media (such as Cl- and organic solvents), and the penetration rate is reduced by more than 60% compared with traditional coatings;
[0039] Mechanical reinforcement: one-dimensional materials improve the impact resistance (verified by experiments, 70 cm drop hammer without damage), wear resistance (verified by experiments, wear ≤8 mg / 50 turns), and particle erosion resistance by 3 times, effectively dealing with the long-term erosion of suspended solids in chemical wastewater.
[0040] 2. Low viscosity solvent-free system, rapid construction at room temperature:
[0041] A low viscosity epoxy resin and modified amine curing agent system is developed, with a solid content of ≥98%, solving the high viscosity construction problem of traditional solvent-free coatings:
[0042] Convenient construction: low-pressure airless spraying (pressure 0.4-0.6 MPa) can be directly used at room temperature (5-35°C), without the need for heating or dilution. It has been verified that the construction efficiency is improved by 50%, and the single shift team daily construction area can reach 500㎡;
[0043] Rapid film formation: the surface drying time is ≤7 hours at 25°C, and full-load curing only takes 2.5 days, and thick coating (0.5-1 mm) has no pinhole and sagging defects, suitable for emergency repair scenarios.
[0044] 3. Functional pigment and filler adaptation, resistant to complex medium erosion:
[0045] For the multiphase corrosion environment of chemical wastewater (acidic ions, organic solvents, high temperature and humidity), a complex pigment and filler (ceramic powder, silane coupling agent, and hydrophobic nanoparticles) is selected:
[0046] Chemical corrosion resistance: tested by experiment, no swelling after 1000h immersion in 5% hydrochloric acid and toluene, and the electrochemical impedance value is always >1×10 10 Ω·cm 2 , which is 3 times better than traditional epoxy coating;
[0047] Hydrophobic and anti-permeation: surface contact angle ≥110°, reducing sewage retention and microbial adhesion, avoiding synergistic damage of electrochemical corrosion and biological corrosion;
[0048] Interface strengthening: silane coupling agent enhances the chemical bonding of the coating with concrete / metal substrate. Tested by experiment, the adhesion is ≥2.5MPa (concrete), 12MPa (metal), respectively, and the peel strength is increased by 40%.
[0049] 4. Multi-scene adaptive process, customized protection scheme:
[0050] Based on the adjustability of material formula and construction parameters, cross-industry and multi-substrate customized protection is realized:
[0051] Substrate adaptation: compatible with concrete (after crack repair), carbon steel, stainless steel and other substrates, no additional interface treatment agent is needed;
[0052] Environmental adaptation: adapt to temperature fluctuations of-20℃-80℃, humidity environment of more than 95%, and extreme scenarios such as marine salt spray (1000h without pitting), landfill leachate (resistant to NH4 + , S 2- erosion) and other extreme scenarios;
[0053] Structural adaptation: low-pressure airless spraying process can cover the inner wall of the pipeline (diameter ≥300mm), pool body corners, welds and other complex structures.
[0054] 5. Green and environmentally friendly process, safe and efficient construction:
[0055] The whole process uses solvent-free and VOC-free formula, which meets the "Technical Requirements for Low Volatile Organic Compound Content Coating Products" (GB / T38597-2020):
[0056] Environmentally friendly: no irritating odor during construction, tested by experiment, waste paint can be treated as general solid waste, and the amount of hazardous waste is reduced by 90% compared with traditional solvent-based paint;
[0057] Safe and reliable: avoid the risk of flammable and explosive organic solvents, no special explosion-proof measures are needed in the construction environment, and water-based cleaning agent is used to reduce the health hazards to operators;
[0058] Economical: tested by experiment, can reduce the waiting time for base layer drying (allowing the moisture content of the substrate to be ≤8%), eliminate the primer process, shorten the overall construction period by 30%, and reduce the whole life cycle cost by more than 40% compared with traditional solutions.
[0059] 6. Long-term sealing performance, long maintenance cycle:
[0060] The coating has excellent compactness (porosity <1%) and the structure stress is optimized to realize the double protection of "zero penetration + anti-cracking":
[0061] Long-lasting sealing: no leakage for 24 hours through water pressure test (0.6 MPa) of 1.5 times the design pressure;
[0062] Cracking resistance: no cracking of the coating when the substrate shrinks by 5%, suitable for dynamic load environment such as soft soil foundation settlement, reducing the frequency of later maintenance, and no need for large-scale renovation within the corrosion period (20 years). BRIEF DESCRIPTION OF DRAWINGS
[0063] Figure 1 The protective ceramic coating is sprayed on the inner wall of the pipeline;
[0064] Figure 2 The protective ceramic coating is sprayed on the inner wall of the water tank. DETAILED DESCRIPTION
[0065] The following description is only a preferred embodiment of the present application, and is not intended to limit the scope of protection of the present application, and any modifications, equivalent replacements and improvements made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
[0066] The following examples can be understood as part of the partial structure or method of the present application, or as a combination of the examples to explain the larger scope of the structure or method of the present application.
[0067] Example 1
[0068] A protective ceramic coating for a corrosive environment is made of the following components by mass percentage: 30%-40% of epoxy resin; 40%-45% of ceramic powder (main components are AI2O3 and SiO2); 10%-25% of nano material surface oxide; 5%-10% of curing agent; 1%-2% of silane coupling agent; 20%-25% of two-dimensional sheet-shaped nano material, and 10%-15% of one-dimensional functional nano material.
[0069] Example 2
[0070] Based on example 1, the present example discloses that the epoxy resin is E-44 and / or E-55, and the mass percentage is 30%.
[0071] Example 3
[0072] Based on embodiment 1, this embodiment discloses that the epoxy resin is E-44 and / or E-55, and the mass percentage is 35%.
[0073] Embodiment 4
[0074] Based on embodiment 1, this embodiment discloses that the epoxy resin is E-44 and / or E-55, and the mass percentage is 40%.
[0075] Embodiment 5
[0076] Based on embodiment 1, this embodiment discloses that the mass percentage of the ceramic powder is 40%.
[0077] Embodiment 6
[0078] Based on embodiment 1, this embodiment discloses that the mass percentage of the ceramic powder is 45%.
[0079] Embodiment 7
[0080] Based on embodiment 1, this embodiment discloses that the two-dimensional sheet-shaped nanomaterial is graphene and / or boron nitride, and the mass percentage is 20%.
[0081] Embodiment 8
[0082] Based on embodiment 1, this embodiment discloses that the two-dimensional sheet-shaped nanomaterial is graphene and / or boron nitride, and the mass percentage is 25%.
[0083] Embodiment 9
[0084] Based on embodiment 1, this embodiment discloses that the one-dimensional functional nanomaterial is carbon nanotube and / or whisker, and the mass percentage is 10%.
[0085] Embodiment 10
[0086] Based on embodiment 1, this embodiment discloses that the one-dimensional functional nanomaterial is carbon nanotube and / or whisker, and the mass percentage is 15%.
[0087] Embodiment 11
[0088] Based on embodiment 1, this embodiment discloses that the mass percentage of the surface oxide of the nanomaterial is 10%, and the curing agent is a modified amine curing agent, and the mass percentage is 5%.
[0089] Embodiment 12
[0090] Based on embodiment 1, this embodiment discloses that the mass percentage of the surface oxide of the nanomaterial is 25%, and the curing agent is a modified amine curing agent, and the mass percentage is 10%.
[0091] Embodiment 13
[0092] Based on example 1, this embodiment discloses that the silane coupling agent is 1% by mass percentage.
[0093] Example 14
[0094] Based on example 1, this embodiment discloses that the silane coupling agent is 2% by mass percentage.
[0095] Example 15
[0096] The base material of the protective ceramic coating is epoxy resin, ceramic powder, nano material surface oxide, silane coupling agent, two-dimensional sheet nano material and one-dimensional functional nano material, and the mass ratio of the base material to the curing agent is 10:7.
[0097] Example 16
[0098] A preparation method of a protective ceramic coating for a corrosive environment comprises the following steps:
[0099] Step 1, raw material pretreatment;
[0100] Step 2, base material preparation;
[0101] Step 3, base material and curing agent compounding.
[0102] Specifically, the step 1 comprises:
[0103] (11) Epoxy resin: preheat in a 40℃ oven for 2 hours to reduce the initial viscosity and avoid insufficient fluidity caused by low temperature;
[0104] (12) Ceramic powder: filter through a 1200 mesh screen to remove agglomerated particles and ensure uniform particle size to improve coating density;
[0105] (13) Two-dimensional sheet nano material: surface modification is performed using 3% to 5% of the mass of the two-dimensional sheet nano material, i.e., stirring the two-dimensional sheet nano material and the silane coupling agent in anhydrous ethanol for 30 minutes at a speed of 500r / min, and then drying at 60℃ for standby (this step can solve the agglomeration problem of nano materials and enhance the interfacial bonding force with the resin);
[0106] (14) One-dimensional functional nano material: surface modification is performed using the same method as step (13) through silane coupling agent;
[0107] (15) Curing agent: 2℃ to 8℃ sealed cold storage, restore to room temperature before use, to avoid the influence of temperature fluctuation on curing activity.
[0108] The step 2 comprises:
[0109] (21) Pre-mixing of epoxy resin and silane coupling agent: add epoxy resin into the container, add silane coupling agent under low-speed stirring at 500 r / min, and stir for 10 minutes (uniform dispersion of silane coupling agent, and pre-activation of the interfacial reactivity of epoxy resin);
[0110] (22) Adding nano-material surface oxide and ceramic powder for primary dispersion: gradually add nano-material surface oxide and ceramic powder into the stirring material obtained in step (21), and increase the stirring speed to 1000 r / min for 2 minutes (to avoid powder agglomeration and preliminarily form a "resin-powder" mixed matrix);
[0111] (23) Adding two-dimensional sheet nano-material into the stirring material obtained in step (22) for high-speed shearing dispersion: first stir at low speed of 800 r / min for 5 minutes to allow the material to be infiltrated, and then increase the speed to 2500 r / min for shearing for 30 minutes (layer-by-layer peeling and uniform distribution of two-dimensional material, and preliminary construction of a physical barrier layer structure);
[0112] (24) Adding one-dimensional functional nano-material into the stirring material obtained in step (23) for stirring and compounding: adjust the stirring speed to 1500 r / min, and stir for 40 minutes (one-dimensional material is uniformly inserted into the matrix to form a "barrier-enhanced" three-dimensional structure with two-dimensional material without obvious agglomeration);
[0113] During the processes of steps (21) to (24), the container is kept at a temperature of ≤50℃ (which can be controlled by ice water bath) to avoid premature curing of the epoxy resin due to high temperature.
[0114] The step 3 comprises:
[0115] (31) Measuring and proportioning: measure the base material and the curing agent according to the mass ratio "base material:curing agent = 10:7" (for example, 1000 g of base material corresponds to 700 g of curing agent);
[0116] (32) Mixing and stirring: slowly pour the curing agent into the base material (to avoid local reaction heat release caused by rapid pouring), and initially stir at 800 r / min for 5 minutes; increase the stirring speed to 1200 r / min, and continuously stir for 15 minutes until the system color is uniform (brown red without obvious stratification or particles);
[0117] (33) Maturation and detection: after mixing, stand for 5 minutes (maturation period), and detect the viscosity (which should be ≤5000 mPa·s at 25℃ to meet the requirements of low-pressure airless spraying); if the viscosity is high, the stirring time can be appropriately prolonged by no more than 10 minutes, and the total operation time needs to be controlled to avoid premature reaction of the curing agent (the construction should be completed within 30 minutes at 25℃ to avoid premature reaction of the curing agent).
[0118] The working principle of the present application (the following data are verified by experiments):
[0119] 1. Nanomaterials composite reinforcement mechanism
[0120] By in-situ polymerization technology, two-dimensional sheet nanomaterials (such as graphene, ceramic sheets) and one-dimensional nanomaterials (such as carbon nanotubes) are combined to form a "layered barrier + fiber reinforced" three-dimensional protective structure. Two-dimensional materials are stacked in the coating to build a dense physical barrier to delay the penetration of corrosion media such as Cl-, SO42-. One-dimensional materials are inserted into the resin matrix to improve the tensile and impact resistance of the coating through bridging, reducing erosion and wear. Surface modification techniques (such as silane coupling agent treatment) are used to solve the agglomeration problem of nanomaterials, enhance the interfacial bonding force between the nanomaterials and the resin, and avoid cracking and falling caused by stress concentration, achieving the synergy of "physical barrier" and "mechanical reinforcement".
[0121] 2. Low viscosity solvent-free system construction
[0122] Design low molecular weight epoxy resin and high activity modified amine curing agent to reduce the viscosity of the system (solid content ≥98% still maintain the construction fluidity), realize the rapid curing at room temperature (initial curing at 20℃ for 8 hours). Optimize the ratio of base material and curing agent (weight ratio 10:7), balance the operation time limit (30 minutes at 25℃) and curing efficiency, and adapt to large area construction. Use low pressure airless spraying technology (pressure 0.4-0.6 MPa), realize uniform coating through high-speed atomization, avoid bubbles and sagging, and form a dense and continuous film layer (single layer 0.25 mm). Preheat the material to above 20℃ in low temperature environment to ensure stable construction performance.
[0123] 3. Performance optimization of functional coating
[0124] Select solvent-resistant pigments and fillers (such as ceramic powder, polytetrafluoroethylene micro powder) and hydrophobic components to build a "chemical barrier + hydrophobic anti-permeation" functional layer to resist toluene, acid ions and other media erosion. Optimize the pigment-to-binder ratio through orthogonal test to improve the hardness (68 HBa) and wear resistance (wear ≤8 mg) of the coating, and reduce the damage of particle erosion. For concrete and metal substrates, respectively enhance the chemical bonding (adhesion ≥2.5 MPa) and interfacial stress design (adhesion ≥12 MPa) through silane coupling agent to ensure strong bonding between the coating and the substrate. After curing, a dense structure without pinholes is formed. Electrochemical test shows that the impedance value is still 3.47×10 10 Ω·cm 2 after 1000h of immersion, blocking the corrosion electrochemical reaction path.
[0125] 4. Curing and construction process control
[0126] The curing time is dynamically adjusted according to the temperature (3 days at 20℃, 2 days at 30℃), the temperature of ≤50℃ is supported to accelerate the curing, and the stress cracking caused by uneven curing inside and outside the thick coating is avoided. During the curing, the resin and the curing agent form a three-dimensional network structure through the ring-opening reaction of epoxy-amine, and the mechanical and chemical properties are simultaneously improved. After the construction defects are treated by local sand blasting (Sa2.5 level), the matching coating is brushed for repair, the chemical compatibility is utilized to realize seamless combination of new and old layers, and the overall protection performance is consistent.
[0127] 5. Material and technical index
[0128] The main material used in the application is a high-adhesion solvent-free ceramic coating, which is composed of a base and a curing agent, and the weight ratio of the two is base:curing agent = 10:7, and the volume ratio is 1:1. The main technical indexes are as follows:
[0129] 5.1 Physical and mechanical properties
[0130] (1) Wear resistance
[0131] A Taber abrasion tester is used, with a load of 1 kg on each side, a rotation speed of 60 r / min, a total rotation of 500 times, and an abrasion of 8 mg.
[0132] (2) Impact strength
[0133] According to the impact resistance test method for paint film in Chinese national standard GB / T1732-1993, the impact height is 70 cm.
[0134] (3) Adhesion
[0135] The adhesion of the coating is tested by a pull-off tester, and the adhesion of the coating is above 12 Mpa.
[0136] (4) Hardness
[0137] A Barcol hardness tester (referred to as Barcol hardness tester) is used for measurement, and the result shows that the hardness of the coating is 68 HBa.
[0138] 5.2 Corrosion resistance
[0139] (1) Salt spray resistance
[0140] According to GB / T10125-2021 "Artificial atmosphere corrosion test salt spray test", the corrosion medium is 5% NaCl solution; the pH is between 6.5 and 7.3; the temperature of the salt water bucket is set to 35±1℃; the temperature of the pressure bucket is set to 47±1℃; the spray amount is 1-2 ml / 80cm2·h; the test period is 1000h, and the spray mode is continuous spraying. The test result shows that when the coating is peeled off, there is no corrosion inside the coating, and the salt spray resistance is more than 1000h.
[0141] (2) Electrochemical test
[0142] A three-electrode system was used, with a saturated calomel electrode as the reference electrode and a platinum electrode as the counter electrode. Data recording and analysis were performed in Versastudio software, and EIS data were fitted in ZSimpWin software. The test frequency was 10000 Hz to 10 mHz, and the perturbation voltage was 50 mv. The results showed that the coating impedance value was 1.6535*1011 ohm*cm after 24 h of immersion, and the coating impedance value was 3.470*1010 ohm*cm after 1000 h of immersion. 2 2
[0143] Table 1, basic physical performance detection index
[0144]
[0145] To sum up, the present application not only provides a reliable long-acting protection solution for chemical wastewater facilities, but also promotes the development of corrosion-resistant materials in the direction of green and high performance, which is of great significance to public safety, resource consumption reduction and the realization of the "double carbon" target.
Claims
1. A protective ceramic coating for use in a corrosive environment, characterized by: It is made of the following components with the mass percentage: 30%-40% of epoxy resin; 40%-45% of ceramic powder; 10%-25% of nano-material surface oxide; 5%-10% of curing agent; 1%-2% of silane coupling agent; 20%-25% of two-dimensional sheet nano-material, 10%-15% of one-dimensional functional nano-material.
2. A protective ceramic coating for use in a corrosive environment according to claim 1, characterized in that: The epoxy resin is E-44 and / or E-55, and the mass percentage is 30% or 35% or 40%.
3. A protective ceramic coating for use in a corrosive environment as claimed in claim 1, characterized in that: The mass percentage of the ceramic powder is 40% or 45%.
4. A protective ceramic coating for use in a corrosive environment as defined in claim 1, characterized in that: The two-dimensional sheet nano-material is graphene and / or boron nitride, and the mass percentage is 20% or 25%.
5. A protective ceramic coating for use in a corrosive environment as defined in claim 1, characterized in that: The one-dimensional functional nano-material is carbon nanotube and / or whisker, and the mass percentage is 10% or 15%.
6. A protective ceramic coating for use in a corrosive environment as defined in claim 1, characterized in that: The curing agent is a modified amine curing agent, and the mass percentage is 5% or 10%.
7. A protective ceramic coating for use in a corrosive environment according to claim 1, characterized in that: The mass percentage of the silane coupling agent is 1% or 2%.
8. A protective ceramic coating for use in a corrosive environment as defined in claim 1, characterized by: In the protective ceramic coating, the total of the base material, which is the epoxy resin, the ceramic powder, the nano-material surface oxide, the silane coupling agent, the two-dimensional sheet nano-material, and the one-dimensional functional nano-material, is in a mass ratio of base material: curing agent = 10:
7.
9. A method of preparing a protective ceramic coating for use in a corrosive environment as claimed in claim 1, characterized in that, It comprises the following steps: Step 1, raw material pretreatment; Step 2, base material preparation; Step 3, base material and curing agent compounding; The step 1 comprises: (11) Epoxy resin: preheat in a 40℃ oven for 2 hours; (12) Ceramic powder: filter through a 1200 mesh screen to remove agglomerated particles and ensure uniform particle size; (13) Two-dimensional sheet nano-material: surface modification with 3%-5% of the two-dimensional sheet nano-material mass of silane coupling agent, i.e., stir the two-dimensional sheet nano-material and the silane coupling agent in anhydrous ethanol for 30 minutes at a speed of 500 r / min, and then dry at 60℃ for standby; (14) One-dimensional functional nano-material: surface modification with silane coupling agent in the same way as step (13); (15) Curing agent: store in a sealed cold storage at 2℃-8℃, and restore to room temperature before use; The step 2 comprises: (21) Epoxy resin and silane coupling agent pre-mixing: add epoxy resin to the container and add silane coupling agent while stirring at a low speed of 500 r / min, and stir for 10 minutes; (22) Add nano-material surface oxide and ceramic powder for primary dispersion: gradually add nano-material surface oxide and ceramic powder to the stirring material obtained in step (21), and increase the stirring speed to 1000 r / min for 2 minutes; (23) Add two-dimensional sheet nano-material to the stirring material obtained in step (22) for high-speed shearing dispersion: first stir at a low speed of 800 r / min for 5 minutes to allow the material to soak, and then increase the speed to 2500 r / min for shearing for 30 minutes; (24) Add one-dimensional functional nano-material to the stirring material obtained in step (23) for stirring and compounding: adjust the speed to 1500 r / min and stir for 40 minutes; During the steps (21) to (24), the container keeps the stirring material temperature ≤50℃ through temperature control; The step 3 comprises: (31) Metering: Base material and curing agent were weighed according to the mass ratio "base material: curing agent = 10:7"; (32) Mixing and stirring: The curing agent was slowly poured into the base material, initially stirred at 800 r / min for 5 minutes; the stirring speed was increased to 1200 r / min, and stirring was continued for 15 minutes until the color of the system was uniform; (33) Curing and detection: After mixing, it was left for 5 minutes, the viscosity was detected, if the viscosity was high, the stirring time was extended by no more than 10 minutes, the total operation time was controlled, and the curing agent was prevented from reacting in advance.